Electronic Structure and Optical Properties of Cu2ZnSnS4 under Stress Effect - Xiufan Yang; Xinmao Qin; Wanjun Yan; Chunhong Zhang; Dianxi Zhang; Benhua Guo (Crystals, 2022)
By using the pseudopotential plane-wave method of first principles based on density functional theory, the band structure, density of states and optical properties of Cu2ZnSnS4 under isotropic stress are calculated and analyzed. The results show that Cu2ZnSnS4 is a direct band gap semiconductor under isotropic stress, the lattice is tetragonal, and the band gap of Cu2ZnSnS4 is 0.16 eV at 0 GPa. Stretching the lattice causes the bottom of the conduction band of Cu2ZnSnS4 to move toward lower energies, while the top of the valence band remains unchanged and the band gap gradually narrows. Squeezing the lattice causes the bottom of the conduction band to move toward the high-energy direction, while the top of the valence band moves downward toward the low-energy direction, and the Cu2ZnSnS4 band gap becomes larger. The static permittivity, absorption coefficient, reflectivity, refractive index, electrical conductivity, and energy loss function all decrease when the lattice is stretched, and the above optical parameters increase when the lattice is compressed. When the lattice is stretched, the optical characteristic peaks such as the dielectric function shift to the lower-energy direction, while the optical characteristic peak position shifts to the higher-energy direction when the lattice is compressed.